2010
DOI: 10.1007/s12311-010-0158-9
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 Proteins and Spinocerebellar Ataxia Type 1: from Molecular Interaction to Human Neuropathology

Abstract: This mini-review focuses on the possible relevance of 14-3-3 proteins in spinocerebellar ataxia type 1 (SCA1). 14-3-3 proteins are mainly localized in the synapses and neuronal cytoplasm, and seven isoforms have been identified in mammals. This family of proteins was initially identified as adaptor proteins which bind to phosphoserine-containing motifs. Binding motifs and potential functions of 14-3-3 proteins are now recognized to have a wide range of functional relevance. SCA1 is an autosomal-dominant neurod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…When CFP-Wt-14-3-3 was co-expressed with the Atx1 mutants, it invariably appeared in very small quantities and was localised in the cytoplasm. Since Atx1 is a nuclear protein2 and the microscopic detection of interaction between Atx1 and 14-3-3 in transfected cells and in SCA1 affected neurones have been exclusively nuclear3536, we decided to attach a nuclear localisation signal (NLS) to 14-3-3. This allowed us to have sufficient CFP-14-3-3 signal in the nucleus to be able to detect any potential FRET signal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When CFP-Wt-14-3-3 was co-expressed with the Atx1 mutants, it invariably appeared in very small quantities and was localised in the cytoplasm. Since Atx1 is a nuclear protein2 and the microscopic detection of interaction between Atx1 and 14-3-3 in transfected cells and in SCA1 affected neurones have been exclusively nuclear3536, we decided to attach a nuclear localisation signal (NLS) to 14-3-3. This allowed us to have sufficient CFP-14-3-3 signal in the nucleus to be able to detect any potential FRET signal.…”
Section: Resultsmentioning
confidence: 99%
“…Even though predominantly a cytoplasmic protein with no obvious NLS signal, various studies have shown the presence of 14-3-3 in the nucleus, as well as the co-localisation of Atx1 and 14-3-3 in the nucleus3536. Since it is not possible to express constitutively phosphorylated proteins, Atx1 is expected to be present in the cell as a mixed population of unphosphorylated as well as phosphorylated forms (as shown in Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…YWHA genes are abundantly expressed in human brain and mediate signal transduction through binding to phosphoserine-containing proteins (Umahara and Uchihara 2010). YWHA genes have been widely studied for the association with schizophrenia, because their products are involved in many biological processes, especially in neurotransmission (Berg et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They are a family of highly conserved proteins that bind to phospho-serine-containing motifs in target proteins and regulate many intracellular signal transduction pathways that are essential for differentiation, development, growth, apoptosis, and survival [19]. As phosphopeptide-binding proteins, 14-3-3 proteins only interact with S776-phosphorylated (pS776) ATXN1, and their interaction is enhanced by the expansion of the polyglutamine tract in ATXN1 [15].…”
Section: Phosphorylation Of Atxn1mentioning
confidence: 99%